Gastrodiplomacy Turki oleh Zahra Turkish Ice Cream di Indonesia - Anastasia Claudia Sinaga; Rudi Sukandar (Indonesian Perspective, 2019)
In international relations, public diplomacy is used by state actors and non-state actors to introduce cultures in the international sphere to create positive image of the countries. One of instruments of public diplomacy is gastrodiplomacy in which actors introduce cultures through special foods of certain country. One of non-state actors that has implemented gastrodiplomacy is Zahra Turkish Ice Cream, a company operated in several major cities in Indonesia such as in Jakarta, Bekasi, Bandung, and Yogyakarta with nine stores in total to introduce Turkey’s culture and identity. This paper describes Zahra Turkish Ice Cream’s role as a non-state actor in conducting gastrodiplomacy and revealed whether or not Zahra Turkish Ice Cream is able to attract consumers toward Turkey’s culture. This paper employs two concepts; new public diplomacy and gastrodiplomacy. This paper argues that Zahra Turkish Ice Cream has succeeded in introducing Turkey’s culture to its customers.